(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This study explores the expansion of audiovisual media in contemporary performing arts from the perspective of intermedial studies. Drawing on a theoretical and methodological framework based on the work of Rajewsky (2005) and Bruhn and Schirrmacher (2021), it examines how cinema is integrated into live arts, generating new experiences of aesthetic perception. Key concepts such as intermediality, hypermediality, expanded audiovisual formats, and cinematic experience are addressed. The research proposes an analytical model focused on the interactions between media and their impact on the spectator’s experience. This approach allows for a deeper understanding of hybrid practices, particularly those dramaturgies built through audiovisual language and technologies. To apply these concepts and observe their manifestations in specific projects, the study analyzes three case studies that represent different forms of scenic intermediality: Los días afuera (Lola Arias, 2024), Festen (La dramática errante, 2023), and Cosmogony (Gilles Jobin, 2021).